Empowering elementary teachers: Digital mathematics learning resource training center for enhanced classroom instruction - Novitasari, Dwi; Soeprianto, Harry; Kurniati, Nani; Junaidi, Junaidi; Yulis Tyaningsih, Ratna; Agustina, Arianti (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The availability and utilization of Mathematics Learning Resource Centers (LRC) play a crucial role in enhancing the quality of teaching in elementary schools. LRC integrated with IT can assist teachers in designing engaging, interactive, and relevant lessons, while also fostering students’ interest in learning. However, field observations reveal that teachers' access to digital learning resources remains limited, and the integration of technology in mathematics instruction is still suboptimal. To address this issue, the program provided training for elementary school teachers on effectively utilizing digital-based learning resource centers. The main objective in this community service is to improve teachers' skills in using LRC as a supportive medium for mathematics instruction in the classroom. The training was conducted through discussions, demonstrations, and hands-on simulations, involving 18 elementary school teachers from Puyung. Evaluation results, obtained through questionnaires, indicate that participants (1) showed high enthusiasm throughout the training, (2) were able to operate the digital LRC independently, and (3) responded positively to the usefulness of LRC in supporting the teaching and learning process. It is expected that this training will broaden teachers’ knowledge and skills in utilizing technology,and contribute to the improvement of mathematics teaching quality at the elementary school level.